A CONFLITUOSA RELAÇÃO DAS ASSEMBLEIAS DE DEUS BRASILEIRAS E A TELEVISÃO: DA PROIBIÇÃO À ACEITABILIDADE - Tomáz, Gilmar Caetano (2015)
This research seeks to analyze and address the ways the televised media within the Assemblies of God churches in Brazil, here researched, mentioned herein plural in will present due to the many denominational ramifications, in their constructions of symbolic representations, imaginary, cultural and media. The aim is to analyze the symbolic dimension on the television usage prohibition among the denominations in question and the arguments for the veto in the midst of the faithful, television s discrete acceptability based on AGs new theological conceptions over the years, investment in free broadcasting Networks (Television Network Boas Novas) and proposal of a televised program as a Denomination s brand name (Pentecostal Movement Program). The adopted methodology for the viability of this research work consists of historical literature research, with its focus on the key issues for the imaginary research s development of the research on the imaginary, identity, culture, nation and television, in addition to documentation research, that has historical records as its aim, which will better elucidate the paths and connection between the television and the Assemblies of God.